Transforming the Islamic Religious Education Curriculum Through a Digital and Contextual Approach - Pujianti, Etika; Husaini, Fahri; Batubara, Abdul Rohimil Mahdi; Ridhoan, Ahmad; Kusmahadi, Kusmahadi; Hasibuan, Nur Annisa; Atmasari, Siti (International Journal on Advanced Science, Education, and Religion, 2025)
The transformation of the Islamic Religious Education (PAI) curriculum is an urgent necessity in facing the digital era and global disruption. The PAI curriculum can no longer focus solely on the transfer of normative knowledge but must also be responsive to technological developments and the demands of 21st-century competencies. This study aims to analyze strategies for transforming the PAI curriculum through digital and contextual approaches and to propose an applicable, transformative, and relevant curriculum model for modern education. The research employed a library research method by analyzing relevant primary and secondary sources, including books, journals, and recent research reports. The findings indicate that the integration of digital technology into the PAI curriculum enhances students' digital literacy, creativity, collaboration, and critical thinking skills. Meanwhile, the contextual approach plays a significant role in connecting Islamic values ​​with the social and cultural realities of Indonesia's plural society. In conclusion, a PAI curriculum that combines digital and contextual approaches not only increases the relevance of religious education but also shapes inclusive, adaptive, and competitive Muslim generations in the global era. The study recommends teacher training in digital literacy, the provision of adequate educational infrastructure, and the design of teaching materials that balance normative aspects with 21st-century skills